2017
DOI: 10.1155/2017/9096829
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 Induces an Epitope Masking ofγc Protein in IL-7 Receptor Signaling Complex

Abstract: IL-7 signaling via IL-7Rα and common γ-chain (γc) is necessary for the development and homeostasis of T cells. Although the delicate mechanism in which IL-7Rα downregulation allows the homeostasis of T cell with limited IL-7 has been well known, the exact mechanism behind the interaction between IL-7Rα and γc in the absence or presence of IL-7 remains unclear. Additionally, we are still uncertain as to how only IL-7Rα is separately downregulated by the binding of IL-7 from the IL-7Rα/γc complex. We demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Indeed, we found that sγc directly interacts with membrane IL‐2 receptors and interfere with ligand/receptor interaction. Altogether with current study and our previous reports, we propose that sγc produced upon TCR stimulation competes with mγc to bind IL‐2Rβ and opposes formation of signaling competent heterotrimeric IL‐2/IL‐2Rβ/mγc complexes. In fact, recent reports using immunofluorescence co‐patching and FRET analysis documented that mγc and IL‐2Rβ already can form 1:1 heterodimeric complexes even in the absence of IL‐2 .…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, we found that sγc directly interacts with membrane IL‐2 receptors and interfere with ligand/receptor interaction. Altogether with current study and our previous reports, we propose that sγc produced upon TCR stimulation competes with mγc to bind IL‐2Rβ and opposes formation of signaling competent heterotrimeric IL‐2/IL‐2Rβ/mγc complexes. In fact, recent reports using immunofluorescence co‐patching and FRET analysis documented that mγc and IL‐2Rβ already can form 1:1 heterodimeric complexes even in the absence of IL‐2 .…”
Section: Discussionsupporting
confidence: 89%
“…Membrane-bound IL-7Rα promotes cell growth and proliferation, and it inhibits apoptosis by regulating the IL-7 signaling pathway [ 37 ]. During this process, IL-7 first binds to IL-7Rα and then recruits IL-2Rγ to form a ternary signaling complex [ 39 ], which activates two main downstream signaling pathways, the JAK/STAT5 and the PI3K–AKT signal pathways [ 6 , 7 , 8 ]. Furthermore, IL-7 also induces the activation of mitogen-activated protein kinases (MAPK) pathway [ 40 ] ( Figure 1 ).…”
Section: Biology and Functions Of Il-7 And Il-7rmentioning
confidence: 99%